2018
DOI: 10.1136/bmjopen-2017-019635
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of ki67 in BCG-treated non-muscle invasive bladder cancer: a meta-analysis and systematic review

Abstract: ObjectivesThe aim of this study was to explore the prognostic value of ki67 as a marker in patients with non-muscle invasive bladder cancer (NMIBC) treated with BCG.MethodsStudies were systematically retrieved from the relevant databases (Web of Science, PubMed, Cochrane Library and Embase), and the expiry date was May 2017. The research steps referred to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis statement.ResultsA total of 11 studies that complied with the inclusion criteria were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 45 publications
1
21
0
3
Order By: Relevance
“…The demonstrated relationship between the recurrence-free survival and the survivin expression is consistent with the results of the meta-analysis by Lv et al (HR 1.831, 95% CI, 1.344-2.493, p = 0.009) [34]. Our study also confirms the analyzes performed by He et al which revealed the relationship between the level of Ki-67 protein expression and the recurrence-free survival in the Caucasian population (HR 1.441, 95% CI, 1.014-2.047) [35]. The results of presented study differ from those of the meta-analysis by Zhou et al who did not show a significant relationship between p53 expression and recurrence-free survival in BCG-treated patients (HR 1.400, 95% CI: 0.910-2.160) [36].…”
Section: Discussionsupporting
confidence: 91%
“…The demonstrated relationship between the recurrence-free survival and the survivin expression is consistent with the results of the meta-analysis by Lv et al (HR 1.831, 95% CI, 1.344-2.493, p = 0.009) [34]. Our study also confirms the analyzes performed by He et al which revealed the relationship between the level of Ki-67 protein expression and the recurrence-free survival in the Caucasian population (HR 1.441, 95% CI, 1.014-2.047) [35]. The results of presented study differ from those of the meta-analysis by Zhou et al who did not show a significant relationship between p53 expression and recurrence-free survival in BCG-treated patients (HR 1.400, 95% CI: 0.910-2.160) [36].…”
Section: Discussionsupporting
confidence: 91%
“…The nuclear antigen recognised by the Ki67 antibody is expressed in proliferating cells but absent in resting cells . Since its discovery in 1983 by Gerdes et al , Ki67 assessed by immunostaining has been studied extensively as a prognostic and predictive marker, predominantly in hormone receptor‐positive breast cancer, but also in other tumours . For example, presurgical Ki67 has been shown to be a marker for recurrence‐free survival and, in the neoadjuvant setting, a marker for endocrine‐resistant tumour that may require more aggressive treatment .…”
Section: Introductionmentioning
confidence: 99%
“…1 Since its discovery in 1983 by Gerdes et al, 1 Ki67 assessed by immunostaining has been studied extensively as a prognostic [2][3][4][5][6][7][8][9][10][11] and predictive 4,6,9,12,13 marker, predominantly in hormone receptor-positive breast cancer, but also in other tumours. [14][15][16][17][18] For example, presurgical Ki67 has been shown to be a marker for recurrence-free survival 19 and, in the neoadjuvant setting, a marker for endocrine-resistant tumour that may require more aggressive treatment. 20 Excellent intra-observer reproducibility under controlled pre-analytical and staining conditions 21 has contributed to the body of evidence showing the potential of Ki67 immunohistochemistry assay to be implemented in hospital laboratories as a cost-effective part of clinical management.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of Ki67, a nuclear antigen associated with proliferation, is closely related to the occurrence and development of many tumor diseases. 19 21 Melling et al showed that Ki67 acts as an independent prognostic biomarker in CRC. 22 In the present study, the expression of Ki67 in tumor tissues of the xeno-graft mouse model was analyzed, and the results showed that silencing of SOX18 effectively inhibited Ki67 expression in CRC tissue.…”
Section: Discussionmentioning
confidence: 99%